Nursing diagnosis identification by nurses in burn wards: A descriptive cross‐sectional study - Khajehgoodari, Mohammad (Nurs Open, 2020)
AIM: To identify and document patients' care needs, it is vital to provide quality care services. This study was aimed to describe care needs derived from records of patients with burn and to evaluate whether nurses employed the North American Nursing Diagnosis Association classification to formulate patients' care needs. DESIGN: A descriptive cross‐sectional study. METHODS: In this study using the convenient sampling method, 430 nursing records reviewed in the burn wards. Data were collected using Gordon's checklist. The validity of the checklist assessed by content validity and the reliability of them calculated with inter‐rater and internal consistency. Data analysed by SPSSv.24. RESULTS: The mean number of diagnoses per record was 1.94. The most frequent diagnosis was in the domain of Safety/Protection and the top two prevalent nursing diagnoses in Sina hospital were a risk for infection and risk for falls. From all of the detected diagnostic, about 83% were determinedly not related to one of 247 labels of the North American Nursing Diagnosis Association. Given that nurses provide nursing care as requested by physicians and patient care needs are not assessed and recorded by them, it can be concluded that there was no nursing thinking behind their nursing care.